Research of operation of liquid-gas ejectors with compact and dispersed jets of liquid - Ponomarenko, Vitaliy; Pushanko, Mykola; Khitriy, Yaroslav; Liulka, Dmytro; Babko, Evhen (My University, 2017)
The work of the jet sulphitator ejector of sugar production is analyzed. The tests of a gas-liquid ejector with a compact and dispersed liquid jet in a wide range of changes in geometric characteristics (1.3 ... 11.25) were tested on the test-bench at the laboratory and the range of their optimal values (4 ... 7), which allowed to reach the maximum ejection coefficient, was found experimentally. The ejection coefficient for an ejector with a compact liquid jet is 15 ... 20% lower than for an ejector with a dispersed jet at the same flow rates.The design of a new two-stage ejector with improved expendable characteristics is offered, the basic geometric dimensions are justified. An increase of the ejection coefficient without additional energy penalties is experimentally proved. The field of application of the offered design ejector is not limited to food industry and it is recommended to use in those cases where heat-mass transfer processes take place.
Keywords: кафедра технологічного обладнання та комп’ютерних технологій проектування; liquid-gas ejector; mixing chamber; ejection coefficient; dispersed; compact fluid jet; two-stage ejector; кафедра готельно-ресторанної справи